2008
DOI: 10.1111/j.1445-2197.2008.04654.x
|View full text |Cite
|
Sign up to set email alerts
|

An Audit of Operative Notes: Facts and Ways to Improve*

Abstract: This audit suggests that handwritten surgical notes generate several errors that could lead to confusion when notes are reviewed for further follow up or are produced as evidence in medico-legal disputes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 3 publications
3
53
1
Order By: Relevance
“…The incidence of litigation in trauma and orthopaedics is on the rise [4]. Illegible notes can have a major impact on any surgeon’s defence in medico-legal cases [5]. Typed notes afford a clear and concise operation note which can be interpreted accurately by a large number of people.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of litigation in trauma and orthopaedics is on the rise [4]. Illegible notes can have a major impact on any surgeon’s defence in medico-legal cases [5]. Typed notes afford a clear and concise operation note which can be interpreted accurately by a large number of people.…”
Section: Introductionmentioning
confidence: 99%
“…These include an aide-memoire attached to the operation sheet, poster/ checklist in the operation theatre, or the use of an operative note proforma sheet (handwritten/computerized) [3,6,7]. The use of a proforma alerts the user to fill all the specified criteria with a resultant improvement in compliance to guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of the problem was revealed in the results table [1,2,3]. Despite the fact that some operative notes were written by specialist, results showed that the problem was rampant.…”
Section: Discussionmentioning
confidence: 99%
“…According to the General Medical council (GMC),It is the doctors' duty 1,2 .Operation notes are useful in the management of patients post-operatively, surgical audit and research and an absolute necessity in medico-legal disputes. Lefter et al 3 emphasized the medico-legal importance, stating that patients have the right to have access to their medical records subject to certain conditions 3 . Teaching or training health facilities still remain the place for proper acquisition of skills in writing standard operation notes.…”
Section: Imentioning
confidence: 99%